2021
DOI: 10.3390/electrochem2010006
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemical Reduction of Bicarbonate to Formate Using Tin Catalyst

Abstract: Nowadays, the self-accelerating increase in global temperatures strengthens the idea that the cutting of CO2 emissions will not be enough to avoid climate change, thus CO2 from the atmosphere must be removed. This gas can be easily trapped by converting it to bicarbonate using hydroxide solutions. However, bicarbonate must be converted into a more valuable product to make this technology profitable. Several studies show great efficiency when reducing bicarbonate solutions saturated with pure CO2 gas to formate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…The CO 2 gas was bubbled into the electrolyte solution for 15 min until a pH of 6.8 was achieved, indicative of saturation of CO 2 . Recent studies by other researchers have shown a large increase in the Faradaic efficiency of product formation when a KHCO 3 solution is saturated with CO 2 versus an inert gas. , The CuO x (np)/TiO 2 (np)/HOPG sample was affixed to a sample holder that exposed a fixed area of 200 mm 2 of the sample surface to the solution and was used as the working electrode. A carbon rod was used as the counter electrode with a saturated calomel reference electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The CO 2 gas was bubbled into the electrolyte solution for 15 min until a pH of 6.8 was achieved, indicative of saturation of CO 2 . Recent studies by other researchers have shown a large increase in the Faradaic efficiency of product formation when a KHCO 3 solution is saturated with CO 2 versus an inert gas. , The CuO x (np)/TiO 2 (np)/HOPG sample was affixed to a sample holder that exposed a fixed area of 200 mm 2 of the sample surface to the solution and was used as the working electrode. A carbon rod was used as the counter electrode with a saturated calomel reference electrode.…”
Section: Methodsmentioning
confidence: 99%
“…The role of bicarbonate in the eCO 2 R has been continuously studied and debated. On the one hand, some reports claimed that bicarbonate is reduced in pure (or saturated with CO 2 ) bicarbonate electrolytes acting as a substrate of the electrochemical reduction reaction [62–64] . Later on, bicarbonate was identified as a carbon donor, releasing CO 2 from the equilibrium near the active sites, and CO 2 being the actual substrate of the reaction.…”
Section: Post‐capture Electrochemical Co2 Conversionmentioning
confidence: 99%
“…As described in our previous studies [ 2 , 3 ] using membrane technology, CO 2 can be trapped by making it react with a sodium hydroxide solution, which converts it into bicarbonate. However, with direct air capture, the saturation of the absorbent solution will take a very long time, and thus the conversion of the CO 2 in the solution to formic acid will be affected in terms of the reaction’s velocity, as we described previously [ 6 ]. Most studies have performed this reaction under ideal conditions in which they pre-saturated the solution by bubbling pure CO 2 [ 7 ], but this does not reflect the real application with atmospheric CO 2 .…”
Section: Introductionmentioning
confidence: 99%